In Vitro Seed Culture as Simple and Rapid Method for Screening Rice (Oryza sativa L.) Cultivars Tolerance to Water Stress: Hasanein S. Oleiwi* Muslim A. Abdulhussein** Maher H. Salman * - سليم عليوي حسنين; عبد علي عبد الحسين مسلم; حميد سلمان ماهر (Journal of Kerbala for Agricultural Sciences, 2017)
This study was performed to study the Effects of in vitro water stress on some growth characters of two rice( Amber33 and Mishkhab2) cultivars. A mature seeds of two rice cultivars( Amber 33 and Mishkhab2) were cultured on Murashige and Skoog medium supplemented with with 3 different Polyethylene glycol 6000 (PEG) concentrations (0, 1,2and 3%) for 14 and 21 days to study the effect of water stress on seedling length , root length , fresh weight and dry weight . Results showed that addition of PEG resulted in decreasing means of all studied characters with the increasing of PEG concentration in MS medium. A significant difference recorded between cultivars; Amber33 produced the highest seedling length, fresh and dry weight, root number and root length compared with Mishkhab2. Keywords : Water stress, Rice, in vitro seed culture, PEG *Part of M.Sc. thesis of the first author